(untitled) (Zaporizhzhia Historical Review, 2021)
The main questions that were raised by Mykola Khvylovyj, during the literature discussion in 1925ñ1928 are analyzed in this article. The author focused on the role of Ukraine in Asian renaissance theory and under what circumstances Ukraine could establish itself in the forefront of the creating of 4th hystorical-cultural type of mankindís development.